Association of Sacral Index, Sacral Ratio, and Sacral Curvature with Different Types of Male Anorectal Malformation - Rohit Lal; Zaheer Hasan; Sandip Kumar Rahul; Vinit Kumar Thakur; Tanu Verma (Journal of Indian Association of Pediatric Surgeons)
Introduction: Sacral ratio (SR) is currently the only measurement to quantitatively evaluate sacral development in patients with anorectal malformations (ARMs). This study proposes sacral curvature (SC) and sacral index (SI) as a new indicator to qualitatively assess the sacrum and hypothesizes that sacral development, both quantitatively and qualitatively, can be an indicator to predict the type of ARM. The study aims to investigate the difference of SI, SR, and SC between ARM types and the association with the type of ARM. Materials and Methods: This study was prospectively conducted for 18 months. Male patients with ARMs were enrolled and divided into three groups based on the types of ARM: (1) low ARM, (2) intermediate ARM, and (3) high ARM. SI was measured using anterioposterior radiograph (infantogram). SC was measured using lateral radiograph of the sacrum (prone cross-table lateral radiographs). Results: Sixty-three male patients with ARMs were included in the study. SIs were 93.766 ± 8.2309, 99.878 ± 5.832, and 109.481 ± 7.4646 in low, intermediate, and high ARM, respectively (P < 0.0001). The SRs in low and intermediate ARM were significantly higher than that in high ARM (0.728 ± 0.05796, 0.625 ± 0.06577, and 0.547 ± 0.6702, P < 0.0001). SCs were 0.232 ± 0.02663, 0.211 ± 0.01621, and 0.1790 ± 0.02364 in low, intermediate, and high ARM, respectively (P < 0.0001). Conclusions: The higher the rectal level is in an ARM, the lower are the objective measurements of the sacrum. SR was the most common and established parameter to assess the sacral development and its correlation with the level of ARM. However, this study demonstrated that in addition to SR, SC and SI can be a possible predictor for the assessment of the level of ARM.